(untitled) (Fiep Bulletin - online, 2011)
Introduction: Patients with Chagas disease often have high blood pressure (HBP) as the main co-morbidity. In hypertensive individuals with and without Chagas disease hypertension control is generally medicated. Alternative measures of intervention such as aerobic exercise have been recommended as the most effective way to reduce levels of blood pressure. Objective: Compare blood pressure and heart frequency in women with and without Chagas disease undergoing a physical training program. Methods: Nineteen volunteers divided in the groups G1 (nine with Chagas disease) and G2 (ten without Chagas disease) were submitted to a training program for 12 weeks, during 30 to 60 minutes twice a week. The systolic (SBP) and diastolic (DBP) blood pressure and heart frequency (HF) were compared within each group and between groups before and after the effort at the beginning (T0) and twelve (T12) weeks. Results: After 12 weeks of exercise training significant differences were observed in G1 for SBP and DBP before and after effort and HR before effort and in G2 for SBP before and after effort and HF after effort. There was no significant difference between G1 and G2 for all variables. Conclusion: The low-intensity exercise significantly reduces blood pressure in women with Chagas disease, can be performed safely and includes patients with this disease in routine practice of exercises.